Chronic endometritis in cases with recurrent embryo implantation failure - El-Sayed, Samir Mohamed; Tappozada, Tarek Mokhtar; Mansour, Fahd Mohamed; Ali, Eman Sheta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Chronic endometritis (CE) is a cause of recurrent implantation failure (RIF) in patients undergoing intracytoplasmic sperm injection (ICSI). CE is diagnosed based on the presence of plasma cell infiltration of the endometrial stroma in endometrial biopsies. Hysteroscopy may be suggestive of CE while the immunohistochemistry with specific cell markers for CD138 cells has been suggested as a more accurate test for the diagnosis of CE. Methods: This study included 110 patients with recurrent ICSI failure (two or more), despite using good-quality embryos. Hysteroscopy and endometrial biopsy were performed as an outpatient procedure. Immunostaining was then performed using a mouse monoclonal CD138 antibody. The prevalence rate of CE was calculated, and the correlation between hysteroscopic findings and immunohistochemical results was assessed. Results: In the included patients in this study there was 32 cases (29%) were diagnosed as CE by hysteroscopy, while 27 cases (24.5%) were positive by CD138 immunohistochemistry (IHC), and 18 cases (16.36%) were positive for CD138 IHC with hysteroscopic features of CE. The presence of more than one abnormal hysteroscopic features was considered positive for CE rather than single abnormal feature, the sensitivity, specificity, positive and negative predictive values of hysteroscopy would be 22.2%, 98.8%, 85.7%, and 79.6%, respectively. Conclusions: The negative diagnostic value of hysteroscopy is high, the combination of the two diagnostic modalities (hysteroscopy and CD138 IHC) will aid in the detection of most cases of CE.